Designing for performance weighing aesthetics and speed - Hogan, Lara Callender (O'Reilly Media, 2015)
As a web designer, you encounter tough choices when it comes to weighing aesthetics and performance. In this practical book, Lara Hogan helps you approach projects with page speed in mind, showing you how to test and benchmark which design choices are most critical. To get started, all you need are basic HTML and CSS skills and Photoshop experience.